1989
DOI: 10.1002/ajim.4700160602
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of exposure to chemicals in a complex work environment

Abstract: Exposure information was evaluated for two large chemical manufacturing facilities and a research and development center in support of occupational health studies of employees assigned to these facilities. Methodology and rationale underlying the exposure categorization are provided, and descriptive exposure statistics are presented for a sample of 774 employees. Analysis of work patterns and exposure profiles revealed that 1) employee transfers among various production work areas did not follow a predictable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, these diaries are subject to inaccurate recall and thus have limited validity (31)(32)(33). Moreover, they fail to document microactivities such as dermal and hand-tomouth contacts, which are important pathways of exposure in young children.…”
mentioning
confidence: 99%
“…However, these diaries are subject to inaccurate recall and thus have limited validity (31)(32)(33). Moreover, they fail to document microactivities such as dermal and hand-tomouth contacts, which are important pathways of exposure in young children.…”
mentioning
confidence: 99%
“…In females, there was a positive trend in incidences with increasing exposure concentration; however, there were no statistical differences and the incidences were within the NTP historical control ranges. It has been reported that the odds ratios for developing lymphoid and hematopoietic cancers were increased in humans exposed to allyl alcohol (the structurally related unsaturated alcohol) (Ott et al 1989a, b). However, the significance of this correlation was confounded by the exposure of workers to multiple chemicals along with allyl alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The ranking scheme is also supported by industrial hygiene surveys of these and other UCC facilities. Based on estimates of operators' TWA8 EO exposures at the UCC Texas City, Texas, plant, exposure levels in direct oxidation EO production were probably in the range of [10][11][12][13][14][15][16][17][18][19][20] ppm.24 Levels in EO production using the chlorohydrin process were probably somewhat higher, since (1) the technology, construction materials, and work practices were from an earlier era, (2) there was no control room, and (3) the production equipment was indoors. Based on breathing zone samples collected from 1976 to 1978 at the South Charleston and Institute plants, continuous exposure levels in departments using EO were in the order of < 1-3 ppm (possibly an order of magnitude lower than those in production departments).…”
Section: Discussionmentioning
confidence: 99%